The effectiveness of Bantuan Langsung Tunai (Direct Cash Assistance) implementation in enhancing community welfare from the perspective of Islamic economics - Indriyanti, Putri; Qarni, Waizul; Dharma, Budi (Universitas Islam Indonesia, 2024)
IntroductionThe Direct Cash Assistance (BLT) program is a vital government project designed to mitigate poverty and enhance the well-being of low-income households in Indonesia. The BLT program has been launched in Rawa Bening Village, Bandar Subdistrict, Simalungun Regency to offer prompt financial assistance to communities that are at risk.ObjectivesThe objective of this study is to assess the efficacy of the BLT program in Rawa Bening Village by analyzing important factors such as comprehension of the program, precise targeting, promptness, achievement of objectives, and tangible outcomes. Furthermore, it examines the utilization of Islamic economic ideas in the execution of the program.MethodThe research employed a qualitative descriptive approach, which entailed conducting interviews with village officials and aid beneficiaries, as well as making observations and documenting the findings. The data analysis adhered to the methodologies provided by Miles and Huberman, which involved the processes of data reduction, data presentation, and drawing conclusions. The program's success was assessed utilizing the Reference Ratio provided by the Research and Development Agency of the Ministry of Home Affairs.ResultsThe analysis revealed that the BLT program had a quite effective impact on the living conditions of 78.4% of the residents in Rawa Bening Village. Although the program had a high level of efficiency in terms of being timely and accurately addressing its objectives, it only achieved modest success in terms of program comprehension and producing tangible results.ImplicationsThe results emphasize the capacity of direct financial support programs to offer immediate relief and contribute to long-term socio-economic progress. The study emphasizes the significance of improving communication tactics and integrating ongoing feedback systems for policymakers. The utilization of Islamic economic principles, including justice, honesty, welfare, and responsibility, offers a sturdy framework for assessing and enhancing social welfare programs.Originality/NoveltyThis study provides a distinctive viewpoint by incorporating Islamic economic ideas into the assessment of a government assistance program. It adds to the overall comprehension of how cultural and religious factors can improve the efficiency of efforts to reduce poverty.